Structure of reef fish communities in Catalinas Islands and Ocotal beach, North Pacific of Costa Rica - Espinoza, Mario (2005)
The reefs are heterogeneous systems that maintain a high diversity of organisms. Fish community structure varies within and among reefs, so it would be expected that reef structure and heterogeneity should affect fish communities inhabiting reefs. Four reef patches at Catalinas Islands (Sur, La Pared, Roca Sucia and Sombrero) and one in Ocotal beach (10°28’45” N; 85°52’35” W) were studied with visual censuses (July-December 2003). The structure and composition of fishes between Catalinas Islands and Ocotal beach were different, and habitat structure and composition explain most of the variance founded. The presence of the fleshy algae Caulerpa sertularioides in Ocotal, and the corals Tubastrea coccinea and Pocillopora spp. at Catalinas Island explained the variability among sites and how it affected fish community structure and composition. The butterfly fish Johnrandallia nigrirostris, damselfish Microspathodon dorsalis, and surgeon fish Prionurus punctatus were directly correlated with the ahermatipic coral Tubastrea coccinea in Roca Sucia reef, while the angel fish Holacanthus passer was associated to reefs with a major percentage of rocky substrate. Other species such as the damselfish Abudefduf troschelli and Halichoeres dispilus were more abundant at Ocotal, where the algae C. sertularioides dominated. The number and abundance of reef fishes was directly correlated with the rugosity index at the reefs of Roca Sucia and Ocotal, but not at reefs of La Pared and Sombrero